2018
DOI: 10.1177/1362168818770910
|View full text |Cite
|
Sign up to set email alerts
|

The effects of instructor language choice on second language vocabulary learning and listening comprehension

Abstract: The present study examined the interaction effects between teachers’ choice of language in lexical explanation and second language (L2) learners’ proficiency level on the learning of phrasal verbs and listening comprehension in a meaning-focused listening activity. Undergraduate L2 learners with two different levels of proficiency (intermediate and advanced) were assigned to three different conditions. These conditions included (1) code-switching, in which teachers briefly switched to learners’ first language … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 29 publications
(67 reference statements)
3
34
2
Order By: Relevance
“…Learners with a lower level of PVK, however, benefited more from the CS approach than from the L2 approach. This last finding is in line with Lee and Levine (2020), who found that intermediate learners in their study benefited significantly more from CS. Both findings would be supported by Kroll and Stewart's (1994) revised hierarchical model of bilingual memory.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Learners with a lower level of PVK, however, benefited more from the CS approach than from the L2 approach. This last finding is in line with Lee and Levine (2020), who found that intermediate learners in their study benefited significantly more from CS. Both findings would be supported by Kroll and Stewart's (1994) revised hierarchical model of bilingual memory.…”
Section: Discussionsupporting
confidence: 89%
“…Second, allowing learners’ PVK and listening proficiency, assessed at baseline, to interact with the other two predictors (test time points and treatment conditions) in the analysis further addressed the possible limitations arising from the lack of random assignment of students to different treatment groups. Furthermore, our findings, using PVK and listening as separate, continuous variables indexing general language proficiency, provide a clearer picture of how both variables interact with vocabulary learning through listening than previous studies using categorical variables and combined, general proficiency measures (e.g., Hennebry et al., 2013; Lee & Levine, 2020; Tian & Macaro, 2012; Vidal, 2011).…”
Section: Limitations and Future Directionsmentioning
confidence: 47%
See 1 more Smart Citation
“…The results showed that learning occurred in all three conditions and providing additional instruction about target words led to the greatest amount of vocabulary learning. Lee and Levine (2020) also found that both intermediate and advanced EFL learners who received teacher explanation of target words in L1 during listening tasks could acquire more vocabulary than learners who did not receive an L1 explanation. In addition, they found that teacher explanation of word meanings helped intermediate learners have better retention in the long term.…”
Section: Factors That Contribute To Incidental Vocabulary Learningmentioning
confidence: 95%
“…A secondary aim of the present research was to examine whether the use of L1 translation by teachers, and frequency of occurrence, were associated with increased vocabulary learning. Many studies provide evidence that multiple exposures to a word leads to vocabulary acquisition (e.g., Vidal, 2011; Webb, Newton, & Chang, 2013), and research suggests that the elaboration of meaning in spoken and written input positively influences word learning (e.g., Lee & Levine, 2020; Zhao & Macaro, 2016). However, at present there does not appear to be any research that has looked at whether either of these two factors contribute to incidental vocabulary learning through listening to teacher talk.…”
mentioning
confidence: 99%